Assessing candidate metrics for the ecological quality of TFTW (tidal freshwaters in transitional waters) in Ireland using benthic invertebrates. (1st July 2017) - Wilson, J.G.; Dunne, N.; Giltrap, M.
Abstract: There is an obligation under the Water Framework Directive (WFD, 2000/60/EC) not just to establish the ecological status of water bodies, but to ensure that they achieve 'good' quality. However, in some cases, the criteria have been difficult to establish, and one such case is that for Tidal Freshwaters in Transitional Waters (TFTW). In this study, based on 8 systems and 37 TFTW sites around Ireland, there were significant differences in invertebrate benthos, which was largely dominated by freshwater species. The evaluation of ecological status varied significantly across sampling methods which in turn were driven by the character of the substratum. The standard kick-sample method, in riffle conditions, yielded 69 taxa, cores in intertidal soft sediments 21 taxa, and grabs in the subtidal 15 taxa. The salinity (Practical Salinity Scale) at the study sites ranged from 0 to 29.3, although all but 3 were <5, but there was a greater consistency of community composition within a single TFTW across salinities than the converse. Diversity indices followed a similar although not identical pattern, with the Shannon-Weiner index (H′) maxima being 2.24, 1.32 and 1.48 for kick samples, cores and grabs respectively. Average Score Per Taxon (ASPT) scores were much closer, ranging from 4.5 to 6.1, 3.5–6.3 and 3.6–5.2 respectively, and in general, indices which included some measure of species' tolerance performed better than those based on diversity alone, but at the cost, in core and grab samples, of a very low information base (very few species contributing to the calculation). Of those metrics assessed, only ASPT could be put forward as a WFD candidate for quality assessment. Highlights: Benthic invertebrates were samples from tidal freshwaters in transitional waters around Ireland. Kick-samples provided a greater range of species than did grab or core samples. Only ASPT (Average Score Per Taxon) was a sufficiently consistent and robust metric to be a candidate for assessing ecological quality.